PROPOLIS SUPPLEMENTATION - EFFECTS ON PHYSICAL ACTIVITY, SKIN, BONE HEALTH, AND CARDIOVASCULAR FUNCTION: A SYSTEMATIC REVIEW - Paula Folta,; Anna Opalińska,; Cezary Lubas,; Joanna Kłosowska,; Kacper Szeląg,; Karolina Błądzińska,; Maciej Błądziński,; Małgorzata Zach,; Piotr Świerczek,; Antoni Kujawski, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: In recent years, many sports supplements have incorporated several natural ingredients. One notable example is propolis, a bee-derived substance rich in bioactive compounds such as flavonoids, phenolic acids, and vitamins. Research indicates that bee glue has several therapeutic properties, including anti-inflammatory, antioxidant, and immunomodulatory effects. These mechanisms support wound healing, strengthen the immune system, combat respiratory infections, improve both recovery and physical capacity, all of which may collectively lead to enhanced athletic performance.Aim of the study: This study aims to provide a comprehensive analysis of propolis properties. Through a detailed discussion and review of the evidence supporting the beneficial effects of propolis supplementation on the skin, as well as the muscular, skeletal, and cardiovascular systems.Material and method: This article presents the current state of knowledge about the effects of propolis supplementation. A literature review was gathered using PubMed, ScienceDirect, and Google Scholar platforms, with a focus on papers from the last five years. The search included the keywords ‘propolis’, ‘antioxidant activity’, ‘anti-inflammatory’, ‘exercise’, ‘skin regeneration’, and ‘cardiovascular function’.Results: Literature review revealed that propolis emerges as a multi-target phytocomplex that attenuates inflammation, augments antioxidant defenses, and favorably modulates vascular and musculoskeletal function across pre-clinical models. Synergistic effects with exercise, biomaterial carriers, and microbiota-directed strategies underscore opportunities for combination interventions.